Controlled modulation of the dynamics of the Deinococcus grandis Dps N‐terminal tails by divalent metals. (30th January 2023) - Guerra, João P. L.; Blanchet, Clement E.; Vieira, Bruno J. C.; Waerenborgh, João C.; Jones, Nykola C.; Hoffmann, Søren Vrønning; Pereira, Alice S.; Tavares, Pedro
Abstract: DNA‐binding proteins from starved cells (Dps) are small multifunctional nanocages expressed by prokaryotes in acute oxidative stress conditions or during the starvation‐induced stationary phase, as a bacterial defense mechanism. Dps proteins protect bacterial DNA from damage by either direct binding or by removing precursors of reactive oxygen species from solution. The DNA‐binding properties of most Dps proteins studied so far are related to their unordered, flexible, N‐ and C‐terminal extensions. In a previous work, we revealed that the N‐terminal tails of Deinoccocus grandis Dps shift from an extended to a compact conformation depending on the ionic strength of the buffer and detected a novel high‐spin ferrous iron center in the proximal ends of those tails. In this work, we further explore the conformational dynamics of the protein by probing the effect of divalent metals binding to the tail by comparing the metal‐binding properties of the wild‐type protein with a binding site‐impaired D34A variant using size exclusion chromatography, dynamic light scattering, synchrotron radiation circular dichroism, and small‐angle X‐ray scattering. The N‐terminal ferrous species was also characterized by Mössbauer spectroscopy. The results herein presented reveal that the conformation of the N‐terminal tails is altered upon metal binding in a gradual, reversible, and specific manner. These observations may point towards the existence of a regulatory process for the DNA‐binding properties of Dps proteins through metal binding to their N‐ and/or C‐terminal extensions.